Breaking Out of the Bubble Putting Simulation Into Context to Increase Immersion and Performance. (December 2018) - Backlund, Per; Maurin Söderholm, Hanna; Engström, Henrik; Andersson Hagiwara, Magnus; Lebram, Mikael
Objective. Simulation based training with full-size mannequins is a prominent means of training within the healthcare sector.Prehospital missions include all parts of the healthcare process which take place before a patient is handed over to the receiving hospital. This implies that thecontext for prehospital care is varied and potentially challenging or dangerous in several ways. In this article we present a study which exploresimmersion andperformance by emergency medical services (EMS) professionals in in a training situation which takes the specifics of prehospital interventions into account. Methods. The study was carried out as a field experiment at an ambulance unit. The experiment was designed to compare the differences between two types of medical scenarios: basic and contextualized. We analyzed the levels of immersion throughout the scenarios and then team performance was evaluated by independent experts. Both analyses were made by observing video recordings from multiple camera angles with a custom made analysis tool. Results. Our results show that thecontextualization of a medical scenario increases both immersion as measured by the Immersion Score Rating Instrument (ISRI) and team performance as measured by the Global Rating Scale (GRS). The overall ISRI score was higher in the contextualized condition as compared to the basic condition, with an average team wise difference of 2.94 (sd = 1.45). This difference is significant using a paired, two-tailed t-test (p<.001). The GRS score was higher for overall clinical performance in the contextualized scenario with an average team wise difference of 0.83 (sd = 0.83, p=.005). Conclusions. Full-size mannequin simulation based training for EMS professionals may be enhanced by contextualizing the medical scenarios. The main benefits are that the contextualized scenarios better take prehospital medical challenges into account and allow participants to perform better.